Порошковый композиционный материал на основе алюминия для работы в условиях трения и повышенных температур - Шалунов, Е.П.; Архипов, И.В. (Вісник Українського матеріалознавчого товариства, 2013)
Developed powder composite material on the basis of aluminium, consisting 95 wt. % of dispersion-strengthened composite material Al10Mg2C2Al2O3, 3,5 wt. % of aluminium powder brand ASD and 1,5 wt. % of carbon in the form of graphite. It has a high strength at the temperature of 350 °C and has a high resistance to wear. When you receive it uses the method of the reactionary mechanical alloying in attritors.